The Laws of Others: Mandating “Rights Through Travel” Between Discrimination, Moral Hazard, and Irrationality - Ergas, Yasmin (Columbia Journal of Gender and Law, 2016)
In the mid-1970s, shortly after a national referendum enshrined the right to divorce within Italy’s legal framework, the campaign for the liberalization of the country’s prohibitive abortion and contraception regulation took off. Part of the strategy adopted by feminist groups centered on organizing abortion travel. Clinics in London—where abortion had been legalized in 1967 (subject to various conditions, including the opinion of two physicians)—proved amenable to receiving weekly plane-loads of women accompanied by one or two activists. As demand grew and London no longer sufficed, other destinations were added. Until a new law was passed in 1978, unhappily pregnant women continued to meet in a cellar of a Roman working class neighborhood that has long since ceded to gentrification.1 There, they received travel instructions from a group of young feminists. Many of the activists were university students; a few—like the lead organizer, physician Simonetta Tosi—already professionals. Perhaps the women going to London were “learning feminism” at the same time as they were accessing vital services. It’s possible that the travel itself promoted recruitment;2 certainly, it was organized both as a service and as a form of mobilization.